The Semiotic Study of Slametan Ngawandasa Ndinteni: Understanding The Significance of Symbolic Communication in the Modernization Era of East Kasiyan Village - Lasino; Mohamad Sudi; Achmad Naufal Irsyadi; Nadia Amalia; Muwafiqus Shobri (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2023)
In the contemporary world, the dynamics of culture and communication are constantly evolving due to the forces of modernization. Traditional rituals and practices often undergo transformations as societies adapt to new realities. The research aims to analyze symbolic communication in the ritual of Slametan Ngawandasa Ndinteni in the village of East Kasiyan, using a semiotic approach. In the context of modernization, the ritual faces challenges in preserving its meaning and relevance amid social and cultural changes. Therefore, this study seeks to understand the symbolic values embedded in the ritual and the role of symbolic communication in strengthening cultural identity and social cohesion in the community. The research adopts a qualitative approach with semiotic analysis method. This research employs a qualitative research design, aiming to deeply explore the semiotic aspects of Slametan Ngawandasa Ndinteni ritual and its significance in the context of modernization. Data is collected through participatory observation during the implementation of Slametan Ngawandasa Ndinteni, as well as in-depth interviews with 20 participants, they were 5 community figures, 5 local leaders, and 10 cultural practitioners related to the communication. Besides, relevant documents and literature are used to support the analysis. The research findings reveal that Slametan Ngawandasa Ndinteni is a ritual rich in signs and symbols, including language, bodily movements, and ritual objects. These signs form a complex system of symbolic communication, containing profound meanings about tradition, religious beliefs, as well as identity and social relationships in the community.